SENSITIVITAS LARUTAN NANOPARTIKEL CeO2 TERHADAP RADIASI SINAR GAMMA TELETERAPI COBALT-60 - Agus Bashori; Iis Nurhasanah; Zaenal Arifin (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Gamma rays are ionizing radiation that are useful to kill cancer cells through radiation therapy, but radiation would be dangerous if the user escapes scrutiny. In this case the required dosimeter to detect its existence. Practically daily dose allowed for radiotherapy ranges from 1.8 Gy to 2 Gy therefore needed dosimeter capable of detecting a range of doses. This study has been conducted testing sensitivity to gamma radiation to a solution of CeO2 nanoparticles, each of which is synthesized at a temperature of 400°C with a concentration of 2.5 x 10-4 g / ml. CeO2 nanoparticle solution is then analyzed using a UV-Vis spectrophotometer before and after irradiated. Gamma radiation with an energy of 1.33 MV administered at doses varying from 1 Gy to 3 Gy. The test results in the form of UV-Vis absorbance spectrum CeO2 nanoparticle solution which is used as a reference to determine changes in absorbance (ΔA) and value-G. Absorbance spectrum showed absorbance increased to dosing and a strong absorbance occurs at a wavelength of 297 nm for a solution of CeO2 nanoparticles were synthesized at a temperature of 400°C. Sensitivity solution CeO2 nanoparticles seen from the changes absrobansi and value-G. Gamma radiation dosing provide value change in absorbance of about 1.50 x 10-2 to 2.50 x 10-2 and values around 0.095 molJ-1 to 0,439 molJ-1 to a solution of CeO2 nanoparticles were synthesized at a temperature of 400°C. These values indicate that the solution of CeO2 nanoparticles have a sensitivity to gamma radiation.